1976
DOI: 10.1084/jem.144.2.358
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies on the T-lymphocyte population of human milk.

Abstract: Human milk lymphocytes (ML) can be partially purified and propagated in vitro as a means of assessing their immunological function. When exposed to a variety of stimuli known to activate T lymphocytes, ML respond in a unique manner that indicates a selected population of immunocompetent cells. ML are hyporesponsive to to nonspecific mitogens and respond in a reduced manner to histocompatibility antigens on allogeneic cells. In most cases, they are completely unresponsive to C. albicans although blood lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(51 citation statements)
references
References 20 publications
(25 reference statements)
7
43
0
1
Order By: Relevance
“…Several research groups reported CMC to re- (Archambault et al, 1988a,b). Background CPM are generally higher in MGL than in PBMC (Parmely et al, 1976;Concha et al, 1980;Nonnecke and Kehrli, 1985), as demonstrated in the current study. Specifically for CMC, this higher background CPM might be explained by the activating effects of colostrum on leukocytes (Sugisawa et al, 2001;Reber et al, 2006).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Several research groups reported CMC to re- (Archambault et al, 1988a,b). Background CPM are generally higher in MGL than in PBMC (Parmely et al, 1976;Concha et al, 1980;Nonnecke and Kehrli, 1985), as demonstrated in the current study. Specifically for CMC, this higher background CPM might be explained by the activating effects of colostrum on leukocytes (Sugisawa et al, 2001;Reber et al, 2006).…”
Section: Discussionsupporting
confidence: 54%
“…Specifically for CMC, this higher background CPM might be explained by the activating effects of colostrum on leukocytes (Sugisawa et al, 2001;Reber et al, 2006). Overall, MGL, both in cattle and in humans, seem not to react as strong as PBMC when confronted in vitro with mitogens and certain antigens (Parmely et al, 1976;Nonnecke and Harp, 1985;Park et al, 1993), as demonstrated in the present study for the mitogen ConA but not for the antigen TT. However, antigen-induced proliferation strongly depends on the antigen used (Smith and Goldman, 1968;Parmely et al, 1977;Archambault et al, 1988b).…”
Section: Discussionsupporting
confidence: 47%
“…Recent studies of the immunologic composition of human and animal milk have centered on the presence of selected lymphocyte populations in milk (12), migration of lymphoblasts from the gutassociated lymphoid system to the mammary gland (8,13,18,19), and the local production or concentration of immunoglobulins in the mammary gland (1 1).…”
Section: Speculationmentioning
confidence: 99%
“…the substantial number of immune cells observed in colostrum and milk (Parmely et al, 1976) produce IgD specific antibody. The present results can be critically compared with those of Keller et al (1985) who used colostrum rather than milk, plasma rather than sera and a colostrum/plasma ratio which is the reciprocal of the S/M ratio employed in the current study.…”
Section: >68mentioning
confidence: 99%
“…These cells are predominantly macrophages, but include B and T lymphocytes (Parmely, Beer & Billingham, 1976). Breast feeding has been reported to protect the human newborns against gastrointestinal, respiratory and possibly allergic problems; the mechanism is unclear and the observations remain controversial.…”
Section: Introducttonmentioning
confidence: 99%